La gestión de casos como metodología para la conexión de los sistemas sanitario y social en España - Garcés, Jorge (Aten Primaria, 2015)
OBJECTIVE: The aim of this paper is to present the assessment of a case management project, implemented with chronic patients in Valencia, for the integration of health and social care. This project is linked with the ‘Sustainable Socio-Health Model’. LOCATION: Health department 06 in Valencia. PARTICIPANTS: The target groups were chronic patients of 65 years and over. INTERVENTIONS: A non-randomized non-blinded comparative study with an intervention and control group. The intervention consisted in the creation of an interdisciplinary case management team, the use of a common portfolio of resources, and its application to a pilot sample with an intervention period of 6-9 months. MAIN MEASUREMENTS: Diseases (ICD-9), functional capacity, use of health and social resources, satisfaction, unit cost services. RESULTS: There was an increase in the combined use of health and social resources in the intervention group, which included social day centers (21.8% in the intervention group compared to 9.8% in the control group), in coordination with primary care (suggested as the only health resource in 55.4% of cases). There was a decrease in the number of medical visits in the intervention group (43.6% versus 74.5% in the control group). Increased patient satisfaction (55.5% in the intervention group compared to 29.4% in the control group) was observed. At least an extra 4.4% of patients were treated using hospital resources without increasing costs. CONCLUSIONS: Case management using a common unique portfolio of health and social resources can improve the coordination of resources, increases patient satisfaction and increases the capacity of using of hospital resources.